Higher Levels of Secretory IgA Are Associated with Low Disease Activity Index in Patients with Reactive Arthritis and Undifferentiated Spondyloarthritis - Salas-Cuestas, Fabián; Bautista-Molano, Wilson; Bello-Gualtero, Juan M.; Arias, Ivonne; Castillo, Diana Marcela; Chila-Moreno, Lorena; Valle-Oñate, Rafael; Herrera, Daniel; Romero-Sánchez, Consuelo (Frontiers in Immunology, 2017)
Both reactive arthritis (ReA) and undifferentiated spondyloarthritis (uSpA) belong to the group of autoinflammatory diseases- spondyloarthritis. Hypotheses have been proposed about a relationship between the intestinal mucosa and inflammation of joint tissues. The role of immunoglobulin IgA or secretory IgA (SIgA) in the inflammatory and/or clinical activity of patients with spondyloarthritis (SpA) remains poorly understood. Objective: To evaluate the status of total IgA and SIgA, and the association between the levels of SIgA, IgA, IgA anti-Chlamydia trachomatis and anti-Shigella spp. with the disease activity measures, erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) levels, were compared in a cohort of patients with ReA and uSpA and healthy subjects. Methods: This was a cross-sectional study.The serum concentrations of SIgA, IgA anti-Chlamydia trachomatis, anti-Shigella spp., and total IgA were measured. Disease activity was measured in each patient by means of Ankylosing Spondylitis Disease Activity Index (BASDAI) and Ankylosing Spondylitis Disease Activity Score(ASDAS). Statistical analysis did include a as bivariate evaluation, comparisons by Student t-test, Kruskal Wallis test, U Mann Whitney test, with a multivariate evaluation by principal components analysis(PCA). A correlation analysis was carried out using the Pearson correlation coefficient and a linear regression models. All analysis were made using Stata version 11.2® for Windows, R V3.3.21. Statistical significance was defined a p-value <0.05. Results: In all, 46 patients (78.2% men; mean age, 34.8±12.3 years) and 53 controls (41% men; mean age, 32±11.4 years) were included in the study. The mean serum levels of SIgA were higher in SpA patients than in healthy subjects (p<0.001). Only SIgA levels correlated with disease activity: BASDAI (r=-0.42, p=0.0046), ASDAS-CRP (r=-0.37, p=0.014), and ASDAS-ESR (r=-0.45, p=0.0021). The negative correlation between SIgA and all activity indices was higher in HLA-B27-positive patients (BASDAI r=-0.70, p=0.0009, ASDAS-CRP r=-0.58, p=0.0093 and ASDAS-ESR r=-0.57, p=0.0083).The PCA showed three factors: The first component was constituted by variables refer as clinical activity measures; The second did include the serological activity markers and the last component was compounded by age and symptoms time Conclusion: Elevated serum levels of SIgA were found to be related with low disease activity in patients with ReA and SpA